Plasma Local Parameters Measuring in the Low Power Radio-frequency Ion Thruster's Discharge Chamber. (2017) - Kozhevnikov, Vladimir; Khartov, Sergey; Suvorov, Maxim; Cherniy, Ivan
Abstract: This paper presents the results of plasma parameters probe studies in the discharge chamber of low power laboratory ion thruster. The measurement procedure based on the use of triple Langmuir probe placed into the discharge chamber's plasma. During the plasma measurements probe characteristics were collected automatically by data acquisition software created in LabVIEW development environment. In the current paper we discuss the results of the experiment: electron temperature T e distribution and electron number density n e distribution in the plasma in the hemispherical discharge chamber of the low power laboratory ion thruster. The distributions were obtained without applying an accelerating potential in the ion-optical system for different values of the propellant (xenon) mass flow. Results obtained are in good agreement with the similar experimental data presented in publications of other authors.